A Century of Marxist Debates Concerning Capitalism, Imperialism and Imperialist Competition. (1st December 2015) - Omer Moussaly
Abstract : The mechanicist association of capitalism to western imperialism has paved the way for current "globalisation" and "empire" discourses while minimising the importance of the nation-state. Conversely only a small number of neo-Marxists think otherwise, and our paper, by returning to classical Marxist theorists of imperialism, tends to valorise their minority position.